The Use of DQ-BSA to Monitor the Turnover of Autophagy-Associated Cargo - Frost, L.S. (Methods Enzymol, 2016)
There is increasing evidence documenting the critical role played by autophagic and autophagy-associated processes in maintaining cell homeostasis and overall systemic health. Autophagy is considered a degradative as well as a recycling pathway that relies on encapsulated intracellular components trafficking to and fusing with degradative compartments, including lysosomes. In this chapter, we describe the use of DQ(™)-BSA to study autophagosome–lysosome fusion as well as a means by which to analyze hybrid autophagic pathways. Such noncanonical pathways include LC3-associated phagocytosis, better known as LAP. Both autophagosomes and LAPosomes (LC3-associated phagosomes) deliver cargo for degradation. The use of fluorescent DQ(™)-BSA in conjugation with autophagic makers and biomarkers of hybrid autophagy offers a reliable technique to monitor the formation of autolysosomes and LAPo-lysosomes in both fixed- and live-cell studies. This technique relies on cleavage of the self-quenched DQ(™) Green- or DQ(™) Red BSA protease substrates in an acidic compartment to generate a highly fluorescent product.